Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Bisnis Ritel Erablue Di Tangerang - Diky Purba Winata; Adiel Kusuma Anugrah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to determine the effect of service quality on customer satisfaction at Erablue Electronic Shop in Tangerang City. This research uses quantitative methods using SPSS 25 software as a hypothesis test. This study uses a measurement instrument in the form of an interval scale which requires respondents to express the effect of service quality on their satisfaction in shopping, using a Likert scale. The data collection technique used a judgmental sampling method with a sample size of 120. The results of this study indicate that Service Quality has a positive effect on Customer Satisfaction at Erablue Electronic Stores in Tangerang City.